Structured Training Program Assistance to Improve Cardiovascular Endurance (VO2Max) for Recreational Runners - Arfin Deri Listiandi; Syafei, Muhamad; Kusuma, Moh Nanang Himawan; Santiko, Galih Yoga; Pambudi, Yudhi Teguh (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The issue faced by the recreational running community in Banyumas/Purwokerto is the lack of understanding regarding structured training programs to improve cardiovascular endurance (VO2Max), which is essential for long-distance running among recreational runners. So far, runners have been running without a structured training program, resulting in no progress in their training to prepare for races and improve their personal best times. The proposed solution is to provide education and guidance on structured training programs, as well as to practice training forms that can enhance cardiovascular endurance. As a result of this guidance, 55.3% of the 38 participants, who had never practiced speed training before, gained an understanding and began incorporating speed training to improve their VO2Max